PIPELINE RELIABILITY LEVEL FOR THE DIFFERENT COLLAPSIBLE STRATA - Pichugin, S. F.; Vynnykov, P. Yu. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Probabilistic analysis of the loessial collapsible soil deformation modulus in the water saturated for two areas of pipeline laying in the Poltava and Kherson region were performed. Respective distributing laws and statistics were obtained. With help of Ansys finite element simulation was performed in the form of the Monte-Carlo method. Pipeline deformation in the loessial collapsible strata local soaking area was modeled; internal operating pressure and temperature difference were considered. Pipeline failure probability by longitudinal stresses parameter in the fine sand soil was obtained, random functions stochastic apparatus was used. Pipeline failure probability by longitudinal stresses parameter with similar geometric parameters and internal operating pressure simulation results were compared with the base composed by fine sand and loessial collapsible strata 7 and 13 meters.